Interactions of novel pyrazole ligand and its transition metal complexes with CT-DNA and BSA: A combination of experimental and computational studies. (1st February 2023) - Zhang, Nan; Liu, Xiang-rong; Zhao, Shun-sheng; Yang, Zai-wen
Graphical abstract: Four new transition metal complexes (M=Co, Ni, Cu, Zn) were characterized by the single crystals X-ray diffraction analysis. The interaction sites and modes of four complexes with CT-DNA/BSA were studied by experimental and computational methods. Ni(II) complex exhibited excellent antibacterial activities against B. subtilis, S. aureus, E. coli and C. albicans . Abstract: A novel pyrazole acylhydrazone (C11 H11 N5 O, HL ) and its four transition metal complexes [Co(HL )L ]NO3 (C1 ), [Ni(HL )L ]NO3 (C2 ), [Cu(HL )L ]NO3 (C3 ), [Zn(HL )L ]NO3 (C4 ) have been synthesized and characterized. The crystal structures of the above five compounds were studied by single-crystal X-ray diffraction analysis. HL was a triclinic crystal system, crystallized in the P -1 space group, and C1 -C4 were all six-coordinated octahedral mononuclear structures with two ligands providing the NNO donor atoms, and the C 2/ c space group. The kinetic interactions of HL and C1 -C4 with CT-DNA and BSA were determined by UV–vis absorption spectra, fluorescence spectroscopy and microcalorimetry. Furthermore, possible interactions were calculated by molecular docking simulation using available software. The UV–vis absorption spectra measurements indicated that HL and C1 -C4 could bind to CT-DNA by intercalations. Fluorescence spectroscopy suggested that HL and C1 -C4 could bind to BSA through a static mechanism. The microcalorimetric studies showed that the durations of interactions of HL and C1 -C4 with CT-DNA/BSA were all<60 min. The calculated enthalpy, entropy and Gibbs free energy changes were Δ H  < 0, Δ S  < 0 and Δ G  < 0, presenting that all interaction processes were exothermic with spontaneous entropic reduction reactions. The order of binding abilities of the HL and C1 -C4 to CT-DNA was C4  > C1  > C2  > C3  > HL, and the order of binding capacities to BSA was C2  > C3  > C1  > C4  > HL . The molecular docking simulations further verified the "semi-insertion" binding modes of HL and C1 -C4 to CT-DNA and the fluorescence quenching of tryptophan in BSA in the presence of five compounds, which indicated that the interactions of HL and C1 -C4 with DNA/BSA included hydrogen bonding, hydrophobic interactions and electrostatic interactions. In addition, by comparing the antibacterial activities of HL and C1 -C4 against B. subtilis (A), S. aureus (B), P. aeruginosa (C), E. coli (D) and C. albicans (E), it was found the antibacterial activities of C1 -C4 were all higher than that of HL, and the inhibitory effects of C1 -C4 on fungi were better than that of four bacteria. At the maximum concentration of 2 mg/mL, C2 exhibited excellent antibacterial activities against B. subtilis, S. aureus, E. coli and C. albicans .